2022
DOI: 10.15835/nbha50112657
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide nanoparticles biosynthetized improve germination and bioactive compounds in wheat sprouts

Abstract: Metal nanoparticles have many positive effects in improving crop production and productivity and allow for increased germination and rapid crop establishment under field conditions. The metallic nanoparticles applied in this study were copper oxide nanoparticles (CuONPs) biosynthesized using orange peel (Citrus X sinensis) as a reducing agent to avoid or reduce toxicity in wheat seeds and sprouts. This study determined the effect of CuONPs on germination, radicle and plumule length, as well as the production o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
0
2
1
Order By: Relevance
“…In contrast to our findings, research in wheat sprouts indicated that small amounts (0.5 mg/mL) of CuO NPs increased the radicle and plumule length, while higher concentrations (6 mg/mL) had inhibitory effects due to Cu accumulation and phytotoxicity in plant tissue [50]. NPs of CuO reduced the root length of salad and alfalfa [51] and rice [43], inducing backwardness of root growth, greater lignification, and cytotoxicity in root cells of soybean [41].…”
Section: Seedlings Performancecontrasting
confidence: 99%
“…In contrast to our findings, research in wheat sprouts indicated that small amounts (0.5 mg/mL) of CuO NPs increased the radicle and plumule length, while higher concentrations (6 mg/mL) had inhibitory effects due to Cu accumulation and phytotoxicity in plant tissue [50]. NPs of CuO reduced the root length of salad and alfalfa [51] and rice [43], inducing backwardness of root growth, greater lignification, and cytotoxicity in root cells of soybean [41].…”
Section: Seedlings Performancecontrasting
confidence: 99%
“…The CuO-NPs were donated by the Centro de Investigación en Química Aplicada (CIQA), Saltillo, Coahuila, México. The nanoparticle size was 95 nm, hemispherical morphology, dark-looking black-brown powder, with a purity of 99.8%, and they were obtained by green synthesis [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…The literature is quite limited, and most articles focus on the effect of nanomaterials on seed germination [ 26 , 27 , 28 ] and on plant growth parameters [ 29 , 30 ] and less on the effect on bioactive compounds or mineral composition [ 12 , 16 ]. Thus, the aim of our study was to evaluate the impact of Fe and Mn oxides functionalized MWCNTs, as well as of the Fe and Mn oxides, on lettuce ( Lactuca sativa L.) growth, bioactive compounds and mineral accumulation.…”
Section: Introductionmentioning
confidence: 99%